Reliving the Old Dream: Rural Tourism Autobiographical Memory on Behavioral Intention - Zhao, Zhifeng; Li, Zhiwei; Chen, Cai (Frontiers in Psychology, 2022)
This paper evaluates a theoretical model based on hypothesized relationships among four constructs, namely, autobiographical memory (memory rehearsal and memory impact), and place attachment as antecedents of revisit intention and recommendation intention in the context of rural tourism in China. The results of 301 Chinese tourists show that the two dimensions of tourists' autobiographical memory (memory rehearsal and memory impact) affect the tourists' intention to revisit and recommend. Place attachment plays an intermediary role among tourists' autobiographical memory, revisit intention and recommendation intention. Our study is the first time that the structural dimension of autobiographical memory has been applied to rural tourism in China. Theoretical and managerial implications are discussed based on the study results.